(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
The South-South geo-political zone of Nigeria has been identified as one of the regions characterized by low tourism patronage despites her huge natural and cultural attraction assets/opportunities and perceived hospitable disposition of her people. Therefore, this study was carried out to empirically ascertain tourist activities and coastal destination marketing performance in Akwa-Ibom State, South-South Nigeria in terms of tourists’ satisfaction and revisit intention. To carry out the study, a survey method was adopted whereby primary data were obtained from 308 respondents through the questionnaire method. Descriptive and univariate analysis was done using simple percentages, mean score, standard deviation while the Pearson Product Moment Correlation technique was deployed for hypotheses testing. The analyzed data revealed that destination activities were strongly and positively correlated with tourists’ satisfaction and revisit intention. The study concluded that tourist activities correlated positively and significantly with tourists’ satisfaction and revisit intention to the tourist sites in Akwa-Ibom. The study, therefore recommended introduction of other touristic activities such as canoeing/boating, boat regatta, bungee jumping, zip-lining, jet skiing, and sun batting for visitors’ fun and relaxation and the beach sustainability.